Urgensi Pendidikan Agama untuk Pencegahan Perilaku Perundungan pada Remaja di Desa Kubutambahan - Putu Agus Windu Yasa Bukian; I Wayan Sujana (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
The character of today's teenagers is very concerning, where many teenagers freely and easily bully others either by saying bad things, stigmatizing and making enemies of certain individuals. The purpose of this study is to provide religious education for adolescents, especially Hinduism, so that they can prevent bullying behavior towards others. This research method uses a pre-experimental design with a pre-post test design. This study used a sample of 34 adolescents with a sampling technique using stratified random sampling. The data collection instrument used a validated questionnaire to see if bullying behavior was repeated or stopped. The results of this study found that bullying behavior experienced good changes in the second and fourth weeks after being given Hindu religious education, namely it could reduce high-risk behavior to moderate risk and these results were statistically significant with a p value <0.05. The conclusion is that Hindu Religious Education is effective in reducing the prevention of bullying behavior.